2002
DOI: 10.1029/2000wr000149
|View full text |Cite
|
Sign up to set email alerts
|

Isotope study of moisture sources, recharge areas, and groundwater flow paths within the eastern Batinah coastal plain, Sultanate of Oman

Abstract: [1] Oxygen and hydrogen isotope analyses of rainfall samples collected on the eastern Batinah coastal plain of northern Oman between 1995 and 1998 indicate two different principal water vapor sources for precipitation in the area: a northern, Mediterranean source and a southern, Indian Ocean source. As a result, two new local meteoric water lines were defined for the study area. Isotopic analyses of groundwater samples from over 200 springs and wells indicate that the main source of water to the Batinah coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 42 publications
3
98
0
Order By: Relevance
“…Case studies on ascertaining main recharge areas and flow paths of groundwater by altitude effect of oxygen isotope have been carried out successfully overseas [9] . Based on calculation on the equation acquired above, the exposing altitude of spring water sample of HS17 should be in a height of 864 m or higher, but the actual exposing altitude is only 305 m, indicating that spring water of HS17 is from confined aquifer.…”
Section: Analyses Of Hydrogen and Oxygen Stable Isotopes In Water Sammentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies on ascertaining main recharge areas and flow paths of groundwater by altitude effect of oxygen isotope have been carried out successfully overseas [9] . Based on calculation on the equation acquired above, the exposing altitude of spring water sample of HS17 should be in a height of 864 m or higher, but the actual exposing altitude is only 305 m, indicating that spring water of HS17 is from confined aquifer.…”
Section: Analyses Of Hydrogen and Oxygen Stable Isotopes In Water Sammentioning
confidence: 99%
“…Harrington et al [8] studied the spatial and temporal distribution of groundwater recharge in the middle of Australia, and ascertained the evolvement processes of groundwater. Weyhenmeyer et al [9] applied the altitude effect of isotope compositions in rainfall under stable climate conditions, and demonstrated the main recharge area and groundwater flow paths, then evaluated the groundwater recharge rates from the different altitudes. In China, the isotope technology is only used for some groundwater researches at some regions and experimental sites.…”
mentioning
confidence: 99%
“…The hydrogen and oxygen isotope ratios can be measured and compared with estimates derived from an empirical relationship with air humidity values over the supposed source regions and based on meteorological data. Recent applications of this method include Yamanaka et al (2002) for rainfall over Japan and Weyhenmeyer et al (2002) who found that rainfall over Oman could be separated into events with a Mediterranean source and events with an Indian Ocean source. However, this approach has fundamental limitations because it requires detailed analyses of rain samples.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental tracers such as the stable isotopic ratios of oxygen (δ 18 O) and hydrogen (δ 2 H) are a valuable tool identify the sources of groundwater recharge by means of mixing calculations (e.g. de Vries and Simmers 2002;Gemitzi et al 2014;Gibson et al 2005;Liu et al 2004;Liu and Yamanaka 2012;Mizota and Kusakabe 1994;Nakaya et al 2007;Qin et al 2011;Rietti-Shati et al 2000;Weyhenmeyer et al 2002;Wilcox et al 2004) and thus to perform a physically based assessment of the intrinsic vulnerability. Such assessment of intrinsic vulnerability is based on the common hydrogeologic assumption that low permeability layers (i.e.…”
Section: Introductionmentioning
confidence: 99%